The Content of Political Discourse in Cyberspace An Analytical Study of MSP Posts in Facebook for the Legislative Political campaign2021 - وسام بوقلمون (International Journal of Social Communication, 2022)
The study is an investigation of the Algerian political parties use of virtual space for their political activities. It attempts to reveal the new methods employed for the development of content of the political discourse in the Algerian context, especially on Facebook, during the electoral campaigns. The sample under study is constituted by the content of the Movement for society and Peace publications on their Facebook account during legislative elections in 2021. The methodological approach is analytical and descriptive with content analysis as a data gathering tool. The study concluded that the content of the MSP political discourse is lacking the political framing methods needed to structure their content on digital medium during political campaigns.